Anesthesia, brain changes, and behavior: Insights from neural systems biology. (June 2017) - Colon, Elisabeth; Bittner, Edward A.; Kussman, Barry; McCann, Mary Ellen; Soriano, Sulpicio; Borsook, David
Highlights: Evaluation of the short and long-term actions of anesthetic agents on the brain. Alterations in neuronal survival and structure after exposure to anesthetic agents. Changes in the aging and developing brain exposed to anesthetic agents. Neuroimaging techniques to evaluate the effect of anesthetic agents on the brain. Preclinical and clinical evidence of brain changes after exposure to anesthesia. Abstract: Long-term consequences of anesthetic exposure in humans are not well understood. It is possible that alterations in brain function occur beyond the initial anesthetic administration. Research in children and adults has reported cognitive and/or behavioral changes after surgery and general anesthesia that may be short lived in some patients, while in others, such changes may persist. The changes observed in humans are corroborated by a large body of evidence from animal studies that support a role for alterations in neuronal survival (neuroapoptosis) or structure (altered dendritic and glial morphology) and later behavioral deficits at older age after exposure to various anesthetic agents during fetal or early life. The potential of anesthetics to induce long-term alterations in brain function, particularly in vulnerable populations, warrants investigation. In this review, we critically evaluate the available preclinical and clinical data on the developing and aging brain, and in known vulnerable populations to provide insights into potential changes that may affect the general population of patients in a more, subtle manner. In addition this review summarizes underlying processes of how general anesthetics produce changes in the brain at the cellular and systems level and the current understanding underlying mechanisms of anesthetics agents on brain systems. Finally, we present how neuroimaging techniques currently emerge as promising approaches to evaluate and define changes in brain function resulting from anesthesia, both in the short and the long-term.